Some Idioms Used in Ferhengname-yi Sadi Tercumesi and Their Persian Equivalents - San, Funda (ISTANBUL UNIV, 2021)
Ferhengname-yi Sa'di Tercumesi is a didactic text translated into Turkish by Hodja Mes'ud bin Ahmed in 1354/1355 (H.755) from Sa'di's Persian text Bustan written in 1257. Bustan, on which selective and parallel texts have been written both in its period and later on, is an important mesnavi in Persian literature that gives advice on many topics such as morality, education, marriage, and state administration. While Bustan is composed of 4044 couplets, Ferhengname-yi Sa'di Tercumesi has just approximately one thousand couplets. Hodja Mes'ud remarks in the introductory part of the work that he did not use any foreign words in this translation. The text indeed manifests the richness of Turkish vocabulary in the Old Anatolian Turkish period. However, although Hodja Mes'ud claims that he avoided using foreign vocabulary, he also mentions to have stayed with the original script in terms of meaning and structure and the work has traces of some Persian structures and patterns, as it is a translation from Persian. One of these structures is the use of idioms to strengthen expression in the work. In this study, the idioms in the text of Hodja Mes'ud are identidied and similarities between these idioms and their Persian equivalents are shown.
Keywords: Ferhengname-yi Sa'di Tercumesi; Hodja Mes'ud; Bustan; Old Anatolian Turkish; Idioms; Linguistics; Literature